2008
DOI: 10.1152/ajpheart.01317.2007
|View full text |Cite
|
Sign up to set email alerts
|

Epac1 is upregulated during neointima formation and promotes vascular smooth muscle cell migration

Abstract: Vascular remodeling after mechanoinjury largely depends on the migration of smooth muscle cells, an initial key step to wound healing. However, the role of the second messenger system, in particular, the cAMP signal, in regulating such remodeling remains controversial. Exchange protein activated by cAMP (Epac) has been identified as a new target molecule of the cAMP signal, which is independent from PKA. We thus examined whether Epac plays a distinct role from PKA in vascular remodeling. To examine the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 35 publications
4
85
1
Order By: Relevance
“…These results are indicative of laminin-induced cell migration mainly through cAMP/Epac1/Rap1 rather than PKA. Likewise, our results and those of Yokoyama et al (62) found Epac1, in opposition to PKA, increases vascular smooth muscle cell migration. However, Lorenowicz et al (41) reported a contradictory result, in which both PKA and Epac1 operate through two parallel and independent signaling pathways that positively regulate endothelial integrity and endothelial cell migration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are indicative of laminin-induced cell migration mainly through cAMP/Epac1/Rap1 rather than PKA. Likewise, our results and those of Yokoyama et al (62) found Epac1, in opposition to PKA, increases vascular smooth muscle cell migration. However, Lorenowicz et al (41) reported a contradictory result, in which both PKA and Epac1 operate through two parallel and independent signaling pathways that positively regulate endothelial integrity and endothelial cell migration.…”
Section: Discussionsupporting
confidence: 92%
“…cAMP is a pivotal second messenger that regulates a wide range of cellular processes. Signaling through cAMP and PKA has been implicated in cytoskeletal regulation and cell migration depends on cell types (9,30,36,41,62). cAMP also activates the guanine nucleotide exchange factor Epac (exchange protein directly activated by cAMP) that can subsequently activate the small GTPase Rap (9).…”
mentioning
confidence: 99%
“…71 Although this study was performed mainly in vitro and requires further investigation in animal models of vascular remodeling, one could speculate that cAMP-producing agonists such as beraprost might help slow restenosis after angioplasty by inhibiting VSMC migration through EPAC activation. In contrast to the finding of a vasculoprotective effect of EPAC, Yokoyama et al 20 has reported that a synthetic EPAC activator used at high concentrations enhanced rat aortic smooth muscle cell migration. The same group recently extended their observation in vivo showing that vascular injury-induced intimal thickening was significantly inhibited in EPAC1-deleted mice.…”
Section: Regulation Of the Vsmc Proliferation And Migrationmentioning
confidence: 87%
“…17 Also only EPAC1 is upregulated in the area of intimal thickening after injury of mouse femoral artery. 20 Therefore, the dysregulation of EPAC expression, and perhaps an imbalance in the expression of EPAC isoforms observed during cardiovascular remodeling suggest a potential implication of these cAMP-GEFs in cardiovascular disease progression (see below).…”
Section: Epac Proteins Epac Genes and Tissue Distributionmentioning
confidence: 99%
“…We and others have recently shown that Epac proteins have an important role in several cellular processes, including proliferation and apoptosis, possibly by their signalling capacity to ERK and phosphoinositide-3 kinase-dependent Akt (Fang and Olah, 2007;Grandoch et al, 2009). It is important that very recent studies could show an involvement of Epac in cell migration (Mei and Cheng, 2005;Yokoyama et al, 2008;Bastian et al, 2009), although the effects (inhibitory or stimulatory) were not consistent.…”
mentioning
confidence: 98%